Exploração e opressão da força de trabalho feminina e sua luta pela emancipação - Santos, Camila Maria dos (2015)
Through the mediation of theoretical legacy of Marx, Engels and Lukács, as well as studies by contemporary authors of the Marxist tradition that investigates the "female labor force", this dissertation deals with the theme "Exploration and oppression of the female workforce and their struggle for emancipation." Its main objective is to analyze, from the historicalontological foundations of capitalist society, the particularity of the "feminine’s" workforce, their working conditions, social reproduction, and the consequences of the development of this society in their struggle for emancipation. For this purpose, it uses a bibliographic search whose methodological approach is the immanent analysis of the theoretical production used as reference. This research has work as the foundation of the human race and its development in class societies, which demands a sexual division of labor; this produces and reproduces the exploitation and oppression of women. One seeks to demonstrate fundamental relationship of the work in the process of self-construction and mankind emancipation, while considers the organization of work processes in the capitalist mode of production. Data presented denote, historically, the intensity of women's oppression by applying a control policy according to the worker's sex; not equal pay and hiring forms, even when it comes to similar jobs; and, under these conditions, increased insertion of the female labor force in different productive activities and in different continents. This process is most visible in the last decades of the twentieth century, at this time, the capital undertakes a restructuring in the productive sector and a reorganization in its ideological and political system. In this contemporary context, it worsens the job insecurity, deregulation of social rights and diffuses the idea that women are reaching their emancipation, social equality with men. The development of the exploitation and oppression of the female labor force in capitalism leads to the emergence of feminist struggle, which, in its different aspects, find it difficult to identify the greatest oppressor of women: the patriarchy, which is updated by voracious dynamics of capital reproduction. For this reason, parts of the feminist movement have difficulties in redirecting the fight against the patriarchy and recognize the historical and material foundations that support the condition of oppression of the working class. We conclude that the struggle of women for their emancipation needs a direction in search of radical transformation, and it also needs overcoming the historical and material foundations of capitalism that generate their oppression, coupled with the struggle of mankind against the alienated labor.